Kajian Tematis Hadis tentang Kebahagiaan dan Relevansinya dalam Membangun Kesehatan Mental di Era Digital - Misbakhussudur; Mukaromah, Kholila (LPPM IAIN Kediri, 2022)
Happiness has become the main need for humans in living life. Every individual human being is willing to do various kinds of ways to achieve happiness. In the modern digital era, the perspective on happiness is transformed into a more complex one. Based on the problems that exist in the community, the writer is interested in conducting research related to happiness in the perspective of the hadith contained in the Sahi>h Bukha>ri Book. The author conducts conceptual thematic research by collecting hadiths that hint at the theme of happiness. This research includes a literature review which is analyzed descriptively-analytical using a psycho-sufistic approach. The result of this research is that there are hadiths which indicate that happiness is obtained in the Book of Sahi>h Bukha>ri no. 1274, 5933 and 5965. And from these three hadiths the author concludes that the problem of happiness in the digital era is a mere form of negligence in understanding worldly issues. This ultimately affects a person's mental health. Then from these various problems the author concludes that by increasing spirituality and also gratitude for the blessings that Allah SWT. giving to His servant is a means to true (essential) happiness.",